The effect of differential settlements on the dynamic response of the train–track system: A numerical study. (1st April 2015) - Paixão, André; Fortunato, Eduardo; Calçada, Rui
Graphical abstract: Highlights: We used a robust railway track 2D FEM model in non-linear dynamic analyses. The model considers track elements, subgrade layers and train–track interaction. We studied the effect of different track dips in the dynamic response of the system. Different track dips affected different aspects of the train–track interaction. The results can contribute to a more efficient planning of maintenance actions. Abstract: Railway tracks on earthworks with poor geotechnical performance may undergo important differential settlements that amplify the dynamic response of the train–track system, inducing rapid track degradation, lower passenger comfort and higher derailment risk. Because the track substructure is normally inaccessible, these problems are not detected early, are very complex to solve and disrupt normal train operation. To study the influence of settlement profiles on the train–track system, the authors performed a parametric study comprising non-linear dynamic analyses using a FEM model to simulate different scenarios. Some profiles caused important amplifications in the train–track system that were associated to rapid track degradation and derailment risk, while others were associated to lower passenger comfort. Hanging sleepers were found to be strongly associated to critical situations of track degradation. The results were integrated and used in a framework to establish performance indicators that can be useful for planning railway track maintenance works.